Characterisation of structural properties for AlSi10Mg alloys fabricated by selective laser melting. Issue 18 (12th December 2017) - Wang, Lianfeng; Jiang, Xiaohui; Guo, Miaoxian; Zhu, Xiaogang; Yan, Biao
ABSTRACT: Selective laser melting (SLM) is a form of additive manufacturing technology that makes it possible to create complex parts directly from metal powders. This technology offers a good balance between investment costs, range of materials and part quality. In the work, in order to investigate the structural properties of SLM AlSi10Mg alloys, the microstructure, structural performance and tensile fracture morphology of the alloys are analysed. The sample study results indicate good prospects, and the application of SLM in terms of aeronautics is studied to verify the structural properties. The ambient vibration test results show that SLM AlSi10Mg alloys could have a better performance in structural analysis and vibration test than the conventional manufacturing part and the reasons are analysed. This paper is part of a thematic issue on Light Alloys.